IMPLEMENTASI MAQASHID SYARIAH DALAM STRATEGI HARGA BERKEADILAN UNTUK MENINGKATKAN KEUNGGULAN KOMPETITIF BISNIS INTERNET SERVICE PROVIDER (ISP) LOKAL (STUDI KASUS: IRVAN WiFi BLITAR) - Mohammad Saiful Rifai, Mohammad Saiful Rifai (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study analyzes the fair pricing strategy of Irvan WiFi Blitar, a local Internet Service Provider (ISP), through the lens of Maqashid Shariah and its impact on competitive advantage. Facing aggressive competition from national providers, this research uses a descriptive qualitative case study approach, gathering data through in-depth interviews and observations. The findings reveal that Irvan WiFi integrates the five pillars of Maqashid Shariah into its business model: protecting religion (contract transparency), life (price stability), intellect (information accessibility), lineage (safe domestic digital environment), and property (social benefit distribution). This maslahah-based approach creates a unique service differentiation and fosters high customer loyalty, providing a sustainable competitive advantage. The study contributes a theoretical model for MSME resilience in the technology sector by transforming theological values into strategic business instruments. In conclusion, fair pricing serves not only as a profit mechanism but as a foundation for business longevity and community welfare. These results offer a vital reference for local ISPs to thrive amidst corporate hegemony by prioritizing ethical and social value.